Understanding splicing regulation through RNA splicing maps - Witten, Joshua T. (Elsevier Trends Journals, 2011)
Alternative splicing is a highly regulated process that greatly increases the proteome diversity and plays an important role in cellular differentiation and disease. Interactions between RNA-binding proteins (RBPs) and pre-mRNA are the principle regulator of splicing decisions. Findings from recent genome-wide studies of protein–RNA interactions have been combined with assays of the global effects of RBPs on splicing to create RNA splicing maps. These maps integrate information from all pre-mRNAs regulated by single RBPs to identify the global positioning principles guiding splicing regulation. Recent studies using this approach have identified a set of positional principles that are shared between diverse RBPs. Here, we discuss how insights from RNA splicing maps of different RBPs inform the mechanistic models of splicing regulation.